2020
DOI: 10.1534/g3.120.401235
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Diets Used inDrosophilaMicrobiome Research and Introduction of theDrosophilaDietary Composition Calculator (DDCC)

Abstract: Nutrition is a major factor influencing many aspects of Drosophila melanogaster physiology. However, a wide range of diets, many of which are termed “standard” in the literature, are utilized for D. melanogaster research, leading to inconsistencies in reporting of nutrition-dependent phenotypes across the field. This is especially evident in microbiome studies, as diet has a pivotal role in microbiome composition and resulting host-microbe interacti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 36 publications
1
55
0
1
Order By: Relevance
“…Despite the many benefits of using D. melanogaster to investigate a spectrum of biological processes, the range of diets used for fly maintenance across the field can complicate interpretation (16,17). Recently, we showed that diet composition between studies varied greatly in both the amounts and types of components used (i.e.…”
Section: Downloaded Frommentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the many benefits of using D. melanogaster to investigate a spectrum of biological processes, the range of diets used for fly maintenance across the field can complicate interpretation (16,17). Recently, we showed that diet composition between studies varied greatly in both the amounts and types of components used (i.e.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Recently, we showed that diet composition between studies varied greatly in both the amounts and types of components used (i.e. inactive yeast versus brewer's yeast versus yeast extract), which ultimately resulted in diets containing a wider than appreciated range of macro-and micronutrients (17). Many diets are reported as "standard" in the literature as well, often without basis (for example, protein of so-called "standard" on November 1, 2020 by guest http://aem.asm.org/ Downloaded from diets analyzed in our study ranged from 6.33 to 77.93 grams per liter), making interpretation of differences in nutritional environments, and, as a result, nutritionmediated phenotypes difficult (17).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Although the relative concentration of each nutrient in yeast is more constrained than on our synthetic diet, systematic studies have shown that the type and commercial source of yeast can have significant effects on overall dietary composition (Lesperance & Broderick, 2020) and the relationship between lifespan and egg laying (Bass et al, 2007). In Bass et al (2007), the most dramatic lifespan reduction for increasing yeast was found when the fly food was made with a water-soluble extract of yeast that would contain very little, if any, sterols.…”
Section: Standard Yeast-based Media Used In the Laboratory Contains Lmentioning
confidence: 99%
“…All diets were manipulated by altering the dextrose and yeast amounts whilst maintaining as close as possible the same calorie content at 142 Calories g/100 m. Yeast was manipulated as it provides the majority of the protein as well as other non-caloric nutritional requirements (Piper, 2017). Values were confirmed using the Drosophila Dietary Composition Calculator (Lesperance & Broderick, 2020).…”
Section: Methodsmentioning
confidence: 99%